AB0529 Prevalence of Circulating CD4+Cd28null T-Cells is Independently Associated with Disease Damage in Systemic Lupus Erythematosus (SLE) Patients. (10th June 2014) - Ugarte-Gil, M.F.; Sanchez-Zuñiga, C.; Gamboa-Cardenas, R.V.; Aliaga-Zamudio, M.; Zevallos, F.; Mosqueira-Riveros, A.; Medina, M.; Cucho-Venegas, J.M.; Perich-Campos, R.A.; Alfaro-Lozano, J.L.; Rodriguez-Bellido, Z.; Torrealva, H.; et al.
Abstract : Background: CD4+CD28null T-cells are a subset of long-lived cytotoxic CD4+ T-cell with pro-inflammatory functions. This subset is supposed to be caused by chronic immune stimulation by either autoantigens or not. CD4+CD28null T-cells have been associated with cardiovascular morbidity and autoimmune diseases like rheumatoid arthritis, but in SLE patients the information is scarce. Objectives: The aim of this study was to determine whether the CD4+CD28null T-cells are associated with disease damage in SLE patients after considering other possible factors. Methods: This cross-sectional study was conducted in consecutive SLE patients seen in our Rheumatology Department from September 2013 to January 2014. An interview, medical records review, physical examination and laboratory tests were performed. SLE was defined using the ACR criteria. Disease activity was ascertained using the SLEDAI, disease damage with the SLICC/ACR damage index (SDI) and comorbidities with the Charlson Comorbidity Index (CCI). Use of prednisone was recorded as current dose and total time of exposure. Use of antimalarials and immunosuppressives was recorded as current, past or never. CD4+CD28null T-cells frequency was analyzed by flow-cytometry. The association of SDI and CD4+CD28null T-cells was examined by Spearman test. This was followed by multivariable analysis adjusted for age, gender, disease duration, CCI, SLEDAI, use of prednisone, antimalarials and immunosuppressive drugs. All analyses were performed using SPSS 21.0. Results: Ninety four patients were evaluated; their median (IQR) age was 42.0 (36.6-50.2) years, 88 (93.6%) were female; almost all patients were mestizo (mixed Caucasian and Amerindian ancestry). Disease duration was 5.6 (2.5-11.4) years. The SLEDAI was 4.0 (2.0-8.0), the SDI 0.0 (0.0-1.0) and the CCI 1.0 (1.0-1.0). The current dose of prednisone was 5.0 (5.0-10.0) mg/d and the total time of exposure to prednisone was 5.0 (2.0-12.5) years; 68 (72.3%) and 14 (14.9%) were current and former users of antimalarials. Sixty five (69.1%) were current or former users of immunosuppressive drugs. Percentage of CD4+CD28null T-cells was 15.5 (8.7-27.1). In the univariable analysis, the percentage of CD4+CD28null T-cells was positively associated with a higher SDI (Rho=0.29, p<0.001) and remained associated in the multivariable analysis (rate ratio: 1.03, 95% CI: 1.01 to 1.04, p<0.001). Conclusions: In SLE patients, CD4+CD28null T cells are independently associated with disease damage. Longitudinal studies are warranted to determine the predictive value of this association. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1912